Pandangan Islam Terhadap Transplantasi Anggota Badan - Hamra Afroh; Siti Nazwa Aulia Divayanti; Aulia Mufida (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
In this modern era full of progress, there are many new breakthroughs in various aspects, especially in the realm of medicine. Various kinds of issues that attract attention from various circles. The purpose of the research is to deepen and clarify the legal opinion as well as the basic principles, process, and positive impact of limb transplantation on others. The other purpose of the research is to prove the perspective in the Qur'an related to limb transplantation as an effort to understand more about the issue. The method used in this research is through a normative approach to analyze the organ transplant law based on primary and secondary legal sources. Transplantation has been allowed or legalized based on the law, the Law and the scholars through investigation in the form of analysis of the data obtained from the existing problem. The results of the analysis show that in emergency situations, transplantation is legally allowed as long as the donor does not feel harmed, but in terms of commercialization, limb transplantation is still not allowed.